Blue & Buff Charity; or The Patriarch of the Greek Clergy applying for Relief. - Gillray, James, 1756-1815 (Humphrey, H., 1793)
Scholarly notes may be added at a later date.
1 print : col.
Keywords: Caricatures; Cartoons; Great Britain -- Politics and government -- 1760-1820